RNA Interference-Mediated Simultaneous Suppression of Seed Storage Proteins in Rice Grains - Cho, Kyoungwon; Lee, Hye-Jung; Jo, Yeong-Min; Lim, Sun-Hyung; Rakwal, Randeep; Lee, Jong-Yeol; Kim, Young-Mi (Frontiers in Plant Science, 2016)
Seed storage proteins (SSPs) such as glutelin, prolamin, and globulin are abundant components in some of the most widely consumed food cereals in the world. Synthesized in the rough endoplasmic reticulum (ER), SSPs are translocated to the protein bodies. Prolamins are located at the spherical protein body I derived from the ER, whereas, glutelins and globulin are accumulated in the irregularly shaped protein bodies derived from vacuoles. Our previous studies have shown that the individual suppression of glutelins, 13-kDa prolamins and globulin caused the compensative accumulation of other SSPs. Herein, to investigate the phenotypic and molecular features of SSP deficiency transgenic rice plants suppressing all glutelins, prolamins, and globulin were generated using RNA interference (RNAi). The results revealed that glutelin A, cysteine-rich 13-kDa prolamin and globulin proteins were less accumulated but that glutelin B and ER chaperones, such as binding protein 1 (BiP1) and protein disulfide isomerase-like 1-1 (PDIL1-1), were highly accumulated at the transcript and protein levels in seeds of the transformants compared to those in the wild-type seeds. Further, the transcription of starch synthesis-related genes was reduced in immature seeds at 2 weeks after flowering, and the starch granules were loosely packaged with various sphere sizes in seed endosperms of the transformants, resulting in a floury phenotype. Interestingly, the rates of sprouting and reducing sugar accumulation during germination were found to be delayed in the transformants compared to the wild-type. In all, our results provide new insight into the role of SSPs in the formation of intracellular organelles and in germination.